Analisis Faktor yang Mempengaruhi Angka Buta Huruf Melalui Geographically Weighted Regression: Studi Kasus Propinsi Jawa Timur - Andiyono Andiyono; Rokhana Dwi Bekti; Edy Irwansyah (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Analysis of factors that influence the rate of illiteracy can provide important information for education. One such factor is the development of information and communication technology (ICT). Characteristics of illiteracy in East Java showes a spatial pattern. Therefore, to obtain the influencing factors Geographically Weighted Regression spatial modeling (GWR) is utilized. Modeling results indicate that the factors that influence the rate of illiteracy in every location are different. In general, factors influencing literacy rate is the percentage of households which have mobile phone and the percentage of households which access the internet at home.